Modified mullite fiber, preparation method and application in sodium ion battery
By modifying mullite fibers and applying them to sodium ion battery separators, the problems of insufficient safety performance of sodium ion batteries, large consumption of active sodium ions and high cost of separators are solved, and the effect of improving battery safety and circulation performance is achieved.
Patent Information
- Application Number
- CN202411866110.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-18
AI Technical Summary
Existing sodium ion batteries have problems such as insufficient safety performance, large consumption of active sodium ions and high cost of diaphragm.
Modified mullite fibers were prepared by immersing mullite fibers in a mixed solution containing aluminum salt, sodium silicate and sodium sources, and subjected to drying, gelling and heat treatment, and applying them to sodium ion battery separators.
Modified mullite fibers improve the safety and circulation performance of sodium ion batteries, enhance the ionic conductivity and stability of the membrane, and extend the service life of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to modified mullite fibers, a preparation method and application thereof in sodium ion batteries. Background Art
[0002] As the global demand for sustainable energy solutions grows, lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, large-scale energy storage and other fields. However, the shortage of lithium resources and the cost of lithium carbonate are becoming increasingly prominent, and the development of new energy storage systems is urgent. In recent years, low-cost sodium-ion batteries have attracted widespread attention in academia and the business community. Their abundant reserves and similarities with lithium batteries make them expected to fill the gap in the lithium battery industry in the field of large-scale energy storage.
[0003] At present, the non-aqueous organic electrolyte used in commercial sodium-ion batteries is usually an organic carbonate solvent system. However, there are still many problems with this type of electrolyte in actual use. First, the battery of electric vehicles is prone to heat up during operation, which will cause safety problems; second, the conventional ethylene carbonate solvent system electrolyte will form a SEI film on the hard carbon surface, resulting in further consumption of active sodium, affecting the cycle life of the sodium-ion battery; finally, the cost of low-sodium ion battery separators is relatively high.
[0004] In view of this, it is indeed necessary to provide a method that can improve the safety performance of sodium ion batteries and replenish active sodium ions in sodium ion batteries. Summary of the invention
[0005] The purpose of the present invention is to provide modified mullite fiber, a preparation method and application in a sodium ion battery, and to improve the safety performance and cycle performance of the sodium ion battery by introducing the modified mullite fiber into the sodium ion battery.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a method for preparing a modified mullite fiber, comprising:
[0008] The mullite fiber is immersed in a mixed solution containing aluminum salt, sodium silicate and a sodium source, and after the immersion is completed, the mullite fiber is dried and gelled in sequence;
[0009] The gelled mullite fiber is heat treated to obtain modified mullite fiber.
[0010] In an optional embodiment, at least one of the following features ac is satisfied:
[0011] a. The pH of the mixed solution is 9-11;
[0012] b. The mass ratio of aluminum salt, sodium silicate and sodium source in the mixed solution is (60-80): (10-15): (1-3);
[0013] c. The mass fraction of the solvent in the mixed solution is 4%-5%;
[0014] In an optional embodiment, at least one of the following features AD is satisfied:
[0015] A. The immersion time is 1h-3h, and the mass ratio of mullite fiber to mixed solution during immersion is (1.8-2.2):3;
[0016] B. The drying temperature is 70℃-90℃ and the drying time is 8h-12h;
[0017] C. The gelation temperature is 18℃-25℃, and the gelation time is 24h-48h;
[0018] D. The heat treatment temperature is 600℃-1200℃, and the heat treatment time is 4h-8h.
[0019] In a second aspect, the present invention provides a modified mullite fiber prepared by the method described in any one of the aforementioned embodiments.
[0020] In a third aspect, the present invention provides a coating for a sodium ion battery separator, comprising 20-30 parts by weight of the modified mullite described in the aforementioned embodiment, 5-10 parts by weight of carbon nanotubes and 3-5 parts by weight of nanocellulose.
[0021] In an optional embodiment, the present invention further comprises 3-10 parts by weight of a binder, wherein the binder is selected from at least one of carboxymethyl cellulose, polyvinyl alcohol and pregelatinized starch;
[0022] And / or, it further comprises 0.3-0.8 parts by weight of a dispersant, wherein the dispersant is selected from at least one of sodium polyacrylate and polyvinyl pyrrolidone.
[0023] In a fourth aspect, the present invention provides a separator for a sodium ion battery, comprising a base film and the coating as described in the aforementioned embodiment, wherein the coating is disposed on the surface of the base film.
[0024] In an optional embodiment, the base film is a polyolefin porous film;
[0025] And / or, the coating has a thickness of 3 μm-6 μm.
[0026] In a fifth aspect, the present invention provides a sodium ion battery comprising the diaphragm described in the aforementioned embodiment.
[0027] In a sixth aspect, the present invention provides an electrical device comprising the sodium ion battery described in the aforementioned embodiment.
[0028] The present invention has the following beneficial effects:
[0029] The present invention modifies mullite fibers, and through a sol-gel method, cations (mainly calcium ions) between mullite fiber layers can be replaced with sodium ions. When applied to sodium ion batteries, the ionic conductivity and stability of the diaphragm can be improved. The modified mullite fibers have good uniformity of distribution in the coating, and can supplement the sodium ions consumed by forming a SEI film during the operation of the sodium ion battery, which is beneficial to improving the battery capacity and extending the service life. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0031] The present invention also provides a method for preparing modified mullite fiber, comprising:
[0032] The mullite fiber is immersed in a mixed solution containing aluminum salt, sodium silicate and a sodium source, and after the immersion is completed, the mullite fiber is dried and gelled in sequence;
[0033] The gelled mullite fiber is heat treated to obtain modified mullite fiber.
[0034] Mullite is a high-strength, high-temperature resistant material, and it has the advantages of uniform expansion, excellent thermal shock stability, high load softening point, small high-temperature change value, high hardness, and good chemical corrosion resistance. It can be applied to sodium ion battery diaphragms to improve the thermal safety of the diaphragm. At the same time, compared with the price of high-silica glass fiber, the price of high-purity mullite fiber powder of 3.2 yuan per kilogram can greatly reduce the cost. At the same time, the present invention uses mullite fiber as a raw material, and the specific aspect ratio of the mullite fiber can be 10-30. Using mullite fiber instead of mullite spheres as a raw material is more conducive to improving the tensile strength of the coating.
[0035] The present invention modifies the mullite fiber, and can replace the cations (mainly calcium ions) between the mullite fiber layers with sodium ions, thereby increasing the number of movable ions, facilitating a more uniform distribution of ions, and reducing the obstacles to ion migration. The modified mullite fiber obtained by the sol-gel method has good uniformity and high purity, and the sol-gel method is convenient for adjusting the structure of the modified mullite fiber. When applied to sodium ion batteries, the ionic conductivity and stability of the diaphragm can be improved, and the modified mullite fiber has good uniformity in the coating, which can supplement the sodium ions consumed by the SEI film formed during the operation of the sodium ion battery, and is conducive to improving the battery capacity and extending the service life.
[0036] Specifically, during the modification process, the mullite fiber is immersed in a mixed solution, in which the sodium source can be a water-soluble component such as sodium nitrate and sodium hydroxide, and the aluminum salt can be a water-soluble component such as aluminum nitrate and aluminum chloride. The sodium salt can provide sodium ions, which are introduced into the mullite fiber to replace calcium ions during the entire modification process; the aluminum salt and sodium silicate are dissolved in the solution to form aluminum ions and silicate ions, which undergo hydrolysis reactions under alkaline conditions to produce corresponding hydroxyl complexes, which further undergo condensation reactions to form Al-O-Si bonds to construct a three-dimensional network structure, and during the gelation process, the particles in the sol gradually aggregate and connect to each other to form a stable three-dimensional network structure, which is finally transformed into a gel. The mullite fiber is immersed in the sol, and during the immersion process, the aluminum salt undergoes hydrolysis and condensation reactions to generate aluminum oxides, which supplement and modify the aluminum components on the surface and inside of the mullite fiber. The silicate is also similar, generating silicon oxides to supplement and modify the silicon components on the surface and inside of the mullite fiber. Aluminum oxide and silicon oxide together construct a three-dimensional network structure, improving its stability.
[0037] In an optional embodiment, at least one of the following features ac is satisfied:
[0038] a. The pH of the mixed solution is 9-11, and the pH of the mixed solution can be adjusted by aqueous ammonia, the concentration of aqueous ammonia can be 0.1 mol / L, which is conducive to the hydrolysis of chloride and sodium silicate under this pH condition;
[0039] b. The mass ratio of aluminum salt, sodium silicate and sodium source in the mixed solution is (60-80): (10-15): (1-3), which is sufficient to supplement the mullite with sodium ions, aluminum oxides and silicon oxides;
[0040] c. The mass fraction of the solvent in the mixed solution is 4%-5%. Specifically, the solvent can be water or ethanol. The concentration of the solute in the mixed solution will affect the rate of ion exchange and thus affect the effect of the modification. When the solute concentration is too high or too low, the modification rate will slow down or even stop.
[0041] In an optional embodiment, at least one of the following features AD is satisfied:
[0042] A. The immersion time is 1h-3h, and the mass ratio of mullite fiber to mixed solution is (1.8-2.2):3 during immersion. To a certain extent, extending the immersion time is beneficial for the mixed solution to fully contact with the mullite fiber and infiltrate into the interior of the mullite fiber.
[0043] B. The drying temperature is 70°C-90°C and the drying time is 8h-12h to remove the solvent attached to the mullite fiber.
[0044] C. The gelation temperature is 18℃-25℃, and the gelation time is 24h-48h. During the gelation process, the sol is gradually transformed into gel. The gelation temperature and time will affect the degree of cross-linking of sodium silicate, and then affect the strength and stability of the coating containing modified mullite fiber.
[0045] D. The heat treatment temperature is 600°C-1200°C, and the heat treatment time is 4h-8h. The heat treatment step is beneficial to improve the crystallinity of the modified mullite, and improve the mechanical strength and thermal stability.
[0046] The embodiment of the present invention further provides a modified mullite fiber, which is prepared by the method described in any one of the above embodiments.
[0047] An embodiment of the present invention further provides a coating for a sodium ion battery separator, comprising 20-30 parts by weight of the modified mullite described in the aforementioned embodiment, 5-10 parts by weight of carbon nanotubes, and 3-5 parts by weight of nanocellulose.
[0048] Mullite itself has poor conductivity, which will affect the performance of the battery. Carbon nanotubes are added to the coating to enhance conductivity.
[0049] First, nanocellulose can enhance the physical and chemical stability of the diaphragm, improve its tensile strength and heat resistance, and reduce the degradation rate of the diaphragm under high temperature or extreme conditions; secondly, its high specific surface area and porous structure are conducive to improving the wettability of the diaphragm, thereby improving the charge and discharge efficiency, cycle stability and fire resistance of the battery; finally, since the surface of nanocellulose is rich in hydroxyl groups, it can increase the ion concentration in the battery electrolyte, thereby increasing the diffusion rate of sodium ions. Hydroxyl groups, as a hydrophilic functional group, can form hydrogen bonds with solvents, reducing the binding energy between solvent molecules and lithium ions, thereby increasing the freedom of sodium ions and accelerating the ion migration rate, thereby improving battery performance.
[0050] In an optional embodiment, the present invention further comprises 3-10 parts by weight of a binder, wherein the binder is selected from at least one of carboxymethyl cellulose, polyvinyl alcohol and pregelatinized starch;
[0051] And / or, it further comprises 0.3-0.8 parts by weight of a dispersant, wherein the dispersant is selected from at least one of sodium polyacrylate and polyvinyl pyrrolidone.
[0052] An embodiment of the present invention further provides a separator for a sodium ion battery, comprising a base film and the coating described in the above embodiment, wherein the coating is disposed on the surface of the base film.
[0053] In an optional embodiment, the base film is a polyolefin porous film;
[0054] The thickness of the coating is 3-6 μm.
[0055] The method for preparing the sodium ion battery separator provided by the present invention may include the following steps:
[0056] (1) Preparation of basement membrane.
[0057] (2) Preparation of modified mullite fiber.
[0058] Aluminum nitrate, sodium silicate and sodium nitrate are added to deionized water in sequence and stirred evenly. Ammonia water is used to adjust the pH to 9-11, and the mullite fiber is immersed in the solution. After the immersion is completed, the mullite fiber is taken out and dried in an oven to accelerate the evaporation of the solvent. After drying, the mullite is placed in a closed environment to make it gel by itself, and then heat-treated to obtain the desired modified mullite fiber, which is ground for later use.
[0059] (3) Preparation of sodium ion battery separator.
[0060] The modified mullite, carbon nanotubes, nanocellulose, binder, dispersant and water are mixed evenly, and after ultrasonic treatment, they are coated on the base film. The coating method can be any coating method so that the coating is evenly coated on the base film. After coating, it is dried at 120° C. for 3 minutes to obtain the desired sodium ion battery separator.
[0061] An embodiment of the present invention further provides a sodium ion battery, comprising the diaphragm described in the aforementioned embodiment.
[0062] An embodiment of the present invention further provides an electrical device, comprising the sodium ion battery described in the aforementioned embodiment.
[0063] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0064] Example 1
[0065] This embodiment provides a method for preparing a sodium ion battery separator, which specifically includes:
[0066] Polypropylene was put into a screw extruder at an extruder temperature of 180°C. The extrudate was cooled at 80°C and then heat treated at 100°C for 8 hours. The heat-treated film was longitudinally cold stretched at 60°C with a stretch ratio of 1.8, and then longitudinally hot stretched at 110°C with a stretch ratio of 3.0. The stretched film was heat-set at 105°C for 3 minutes, and then cooled and rolled for use.
[0067] Aluminum nitrate, sodium silicate and sodium nitrate are added to deionized water in a mass ratio of 60:10:2 in sequence, and the mixture is stirred evenly. The pH value is adjusted to 9-11 with 0.1 mol / L ammonia water to obtain a mixed solution, in which the mass fraction of water is 5%. Mullite fiber is immersed in the mixed solution (the mass ratio of mullite fiber to the mixed solution is 2:3) for 2 hours and then taken out. The fiber is dried in an oven at 70°C for 12 hours to accelerate the volatilization of the solvent, and then placed at 25°C for 48 hours to make it gel in a closed environment. Heat treatment is then performed at a temperature of 800°C for 6 hours to obtain the desired modified mullite, which is ground for standby use.
[0068] Modified mullite, carbon nanotubes, nanocellulose, pregelatinized starch, sodium polyacrylate and water are uniformly mixed at a ratio of 20:5:3:3:0.3:70, and then subjected to ultrasonic treatment. After ultrasonication, the slurry is coated on a base film and dried at 120°C for 3 minutes to obtain the desired sodium ion battery separator, wherein the thickness of the base film is 16 μm and the thickness of the coating is 3 μm.
[0069] Example 2
[0070] This embodiment provides a method for preparing a sodium ion battery separator, which is different from Embodiment 1 mainly in that the ratio of modified mullite, carbon nanotubes, nanocellulose, pregelatinized starch, sodium polyacrylate and water is 30:5:3:5:0.5:70.
[0071] Example 3
[0072] This embodiment provides a method for preparing a sodium ion battery separator, which is different from Embodiment 1 mainly in that the ratio of modified mullite, carbon nanotubes, nanocellulose, pregelatinized starch, sodium polyacrylate and water is 30:10:3:10:0.8:90.
[0073] Example 4
[0074] This embodiment provides a method for preparing a sodium ion battery separator, which is different from Embodiment 1 mainly in that the ratio of modified mullite, carbon nanotubes, nanocellulose, pregelatinized starch, sodium polyacrylate and water is 30:5:5:3:0.3:70.
[0075] Example 5
[0076] This embodiment provides a method for preparing a sodium ion battery separator, which is different from Embodiment 1 mainly in that the mass ratio of aluminum nitrate, sodium silicate and sodium nitrate in the mixed solution is 80:10:1.
[0077] Example 6
[0078] This embodiment provides a method for preparing a sodium ion battery separator, which is different from Example 1 mainly in that the mass ratio of aluminum nitrate, sodium silicate and sodium nitrate in the mixed solution is 60:15:3.
[0079] Example 7
[0080] This embodiment provides a method for preparing a sodium ion battery separator, which is different from Embodiment 1 mainly in that the pH value of the mixed solution is 11.
[0081] Example 8
[0082] This embodiment provides a method for preparing a separator for a sodium ion battery, which is different from Embodiment 1 mainly in that the pH value of the mixed solution is 9.
[0083] Comparative Example 1
[0084] This comparative example provides a method for preparing a sodium ion battery separator, which differs from Example 1 mainly in that no carbon nanotubes are added.
[0085] Comparative Example 2
[0086] This comparative example provides a method for preparing a sodium ion battery separator, which is different from Example 1 mainly in that the mullite fiber is not modified by sodium salt replacement.
[0087] Comparative Example 3
[0088] This comparative example provides a sodium ion battery separator, which is a polypropylene-based membrane without coating, as a blank control.
[0089] Comparative Example 4
[0090] This comparative example provides a method for preparing a sodium ion battery separator, which is different from Example 1 mainly in that modified mullite fiber is not added to the coating slurry.
[0091] Comparative Example 5
[0092] This comparative example provides a method for preparing a sodium ion battery separator, which is different from Example 1 mainly in that no aluminum salt is added to the mixed solution.
[0093] Comparative Example 6
[0094] This comparative example provides a method for preparing a sodium ion battery separator, which is different from Example 1 mainly in that no silicate is added to the mixed solution.
[0095] Comparative Example 7
[0096] This comparative example provides a method for preparing a sodium ion battery separator, which is different from Example 1 mainly in that the pH value of the mixed solution is 13.
[0097] Comparative Example 8
[0098] This comparative example provides a method for preparing a sodium ion battery separator, which is different from Example 1 mainly in that the pH value of the mixed solution is 8.
[0099] Comparative Example 9
[0100] This comparative example provides a method for preparing a sodium ion battery diaphragm, which is different from Example 1 mainly in that the preparation method of modified mullite is different, the mixed solution is directly placed in an oven and dried at 70°C for 12 hours to accelerate the volatilization of the solvent, and then placed at 25°C for 48 hours to allow it to gel in a closed environment; then heat treatment is performed at a temperature of 800°C for 6 hours to obtain the desired sodium mullite powder, which is ground for later use.
[0101] Performance Testing
[0102] (1) Liquid absorption rate: Ethyl methyl carbonate and a dimethyl carbonate solution of lithium hexafluorophosphate with a concentration of 1 mol / L were mixed in a volume ratio of 1:1 to prepare an electrolyte. The sodium ion battery separators prepared in the above embodiments and comparative examples were immersed in the electrolyte at 25° C. for 12 h. After the electrolyte was immersed, the excess electrolyte on the surface was taken out and wiped off, and the electrolyte was weighed to calculate the liquid absorption rate.
[0103] (2) Membrane rupture temperature
[0104] The membrane rupture temperature is measured by the resistance mutation method, and the point where the resistance suddenly increases is the membrane rupture temperature.
[0105] (3) Ionic conductivity:
[0106] The bulk resistance was tested by using the steel sheet / diaphragm / steel sheet assembly method and the electrochemical impedance spectroscopy (EIS) mode of the VMP3B-10 electrochemical workstation (Bio-LogicScience Instruments), where the disturbance voltage amplitude was 5 mV and the frequency was 10 mHz to 1 MHz. The relationship between bulk resistance and ionic conductivity is: ionic conductivity = diaphragm thickness / (diaphragm resistance*contact area between diaphragm and electrode)*10 -2 , where the unit of diaphragm thickness is mm, the unit of diaphragm resistance is Ω, and the unit of contact area between diaphragm and electrode is m2.
[0107] (4) Cyclic charge and discharge test:
[0108] The positive electrode is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 composite material, the negative electrode is a sodium sheet with a purity of 99.9%, the electrolyte is still an organic electrolyte with a volume ratio of VPC:VFEC=1:0.06 (propylene carbonate: fluoroethylene carbonate) and a NaClO4 concentration of 1 mol / L, and then it is assembled into a sodium ion battery.
[0109] At 25°C, the battery was first charged and discharged at a rate of 0.3C in the voltage range of 2-4V for 3 cycles, and then charged and discharged at a rate of 1C for 100 cycles.
[0110] The test results of the sodium ion battery separators prepared in the above embodiments and comparative examples are shown in Table 1.
[0111] Table 1
[0112]
[0113] From the comparison between the embodiments in the above table and comparative example 3, it can be seen that the present invention applies modified mullite fiber to the sodium ion battery diaphragm, which can increase the rupture temperature of the diaphragm and improve the safety of the sodium battery. At the same time, it can also extend the service life of the sodium battery and maintain the battery capacity.
[0114] From the comparison of Example 1 and Comparative Examples 2-4, it can be seen that the mullite fiber coating can improve the membrane rupture temperature, liquid absorption rate, ionic conductivity and capacity retention rate to a certain extent, but the modified mullite has a more significant effect on improving the ionic conductivity and capacity retention rate, which may be due to the replacement of calcium ions by sodium ions in the sodium mullite, increasing the number of mobile ions. The distribution of ions is made more uniform, the obstacles to ion migration are reduced, and at the same time, the sodium ions consumed in the formation of SEI film when the battery is used for the first time are supplemented to a certain extent; the comparison between Example 1 and Comparative Example 1 can illustrate that the introduction of carbon nanotubes is beneficial to improving the ionic conductivity and capacity retention rate of the diaphragm; the comparison between Examples 1, 5, 6 and Comparative Examples 5-6 shows that when the mass ratio of aluminum nitrate, sodium silicate and sodium nitrate in the mixed solution exceeds a reasonable range, the reaction will generate aluminum oxide and silicon dioxide precipitated particles, affecting the final performance; the comparison between Examples 1, 7-8 and Comparative Examples 7-8 shows that when the pH of the mixed solution exceeds a reasonable range, the sodiumization process will be slow and the reaction will be incomplete; the comparison between Example 1 and Comparative Example 9 shows that if other methods are used to modify mullite, the tensile strength of the diaphragm will be affected.
[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A coating for a sodium ion battery separator, characterized in that: The invention comprises 20-30 parts by weight of modified mullite fiber, 5-10 parts by weight of carbon nanotubes and 3-5 parts by weight of nanocellulose; wherein the preparation method of the modified mullite fiber comprises: The mullite fiber is immersed in a mixed solution containing aluminum salt, sodium silicate and a sodium source, and after the immersion is completed, the mullite fiber is dried and gelled in sequence; the sodium source is at least one of sodium nitrate and sodium hydroxide, and the mass ratio of the aluminum salt, sodium silicate and sodium source in the mixed solution is (60-80): (10-15): (1-3); The gelled mullite fiber is heat treated to obtain modified mullite fiber.
2. The sodium ion battery separator coating according to claim 1, characterized in that: Satisfies at least one of the following characteristics ab: a. The pH of the mixed solution is 9-11; b. The mass fraction of the solvent in the mixed solution is 4%-5%.
3. The coating for sodium ion battery separator according to claim 1, characterized in that: Satisfy at least one of the following characteristics AD: A. The immersion time is 1h-3h, and the mass ratio of mullite fiber to mixed solution during immersion is (1.8-2.2):3; B. The drying temperature is 70℃-90℃ and the drying time is 8h-12h; C. The gelation temperature is 18℃-25℃, and the gelation time is 24h-48h; D. The heat treatment temperature is 600℃-1200℃, and the heat treatment time is 4h-8h.
4. The coating for sodium ion battery separator according to claim 1, characterized in that: The invention also comprises 3-10 parts by weight of a binder, wherein the binder is selected from at least one of carboxymethyl cellulose, polyvinyl alcohol and pregelatinized starch; And / or, it further comprises 0.3-0.8 parts by weight of a dispersant, wherein the dispersant is selected from at least one of sodium polyacrylate and polyvinyl pyrrolidone.
5. A sodium ion battery separator, characterized in that: The invention comprises a base film and the coating according to any one of claims 1 to 4, wherein the coating is arranged on the surface of the base film.
6. The sodium ion battery separator according to claim 5, characterized in that The base film is a polyolefin porous film; And / or, the coating has a thickness of 3 μm-6 μm.
7. A sodium ion battery, characterized in that: The diaphragm according to claim 6 is included.
8. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 7.
Citation Information
Patent Citations
Mullite fiber / mullite whisker / silicon dioxide aerogel multilevel structure as well as preparation method and application thereof
CN109320193A